The Effect of Balance Ball Exercise On Handling Lower Back Pain In I-Fit Indonesia Members In Central Jakarta - Arifianto, Dimas Indria; Gemael, Qorry Armen; Dewi, R. Retna Kinanti; Wijaya, Habibi Hadi; Setiawan, Muhammad Arief (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to evaluate the effectiveness of Balance Ball Exercise in alleviating lower back pain among members of I-Fit Indonesia, Central Jakarta. Lower back pain, characterized by discomfort and muscle spasms in the lower back, often disrupts the balance between the abdominal and paravertebral muscles, limiting mobility. This condition is prevalent among I-Fit Indonesia members in Central Jakarta. Balance Ball Exercise is an approach that utilizes a stability ball to potentially reduce back pain and strengthen core, gluteal, and back extensor muscles, which may contribute to alleviating symptoms of lower back pain. The research employs a quantitative, one-group pre-test-post-test design with a sample of 12 members from I-Fit Indonesia, selected through purposive sampling. The primary measurement tool, a goniometer, assesses range of motion (ROM) by determining the angle between bone segments at the maximum point of movement. Data analysis includes tests for normality, homogeneity, and hypothesis testing. The results indicate a positive effect of Balance Ball Exercise on managing lower back pain. Analysis using a paired sample t-test shows that balance ball training significantly influences pain reduction, with a significance value of 0.000 (p < 0.05). Paired sample correlations show a low but positive correlation (r = 0.637, p > 0.05), indicating a positive relationship between balance ball training and lower back pain relief. These findings suggest that Balance Ball Exercise can be a beneficial intervention for lower back pain among I-Fit Indonesia members, providing an accessible method to enhance core stability and manage pain.